2015
DOI: 10.1128/aem.00396-15
|View full text |Cite
|
Sign up to set email alerts
|

Prey-Specific Growth Responses of Freshwater Flagellate Communities Induced by Morphologically Distinct Bacteria from the Genus Limnohabitans

Abstract: bBecause their large growth potential is counterbalanced with grazing by heterotrophic nanoflagellates (HNF), bacteria of the genus Limnohabitans, which are common in many freshwater habitats, represent a valuable model for examining bacterial carbon flow to the grazer food chain. We conducted experiments with natural HNF communities taken from two distinct habitats, the meso-eutrophic Ř ímov Reservoir and the oligo-mesotrophic Lake Cep (South Bohemia). HNF communities from each habitat at distinct seasonal ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…We examined the growth potential and biomass transfer efficiency of natural HNF communities feeding on a very broad spectrum of relevant planktonic bacterial groups so far not employed in previous investigations (cf. Šimek et al 2013; Grujčić et al ; Weisse et al ). Moreover, our study has brought new insights into food quality aspects of the prey bacteria and revealed both general and prey‐specific trends in the growth responses of natural HNF communities to changing prey food quality represented by 16 distinct bacterial strains (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We examined the growth potential and biomass transfer efficiency of natural HNF communities feeding on a very broad spectrum of relevant planktonic bacterial groups so far not employed in previous investigations (cf. Šimek et al 2013; Grujčić et al ; Weisse et al ). Moreover, our study has brought new insights into food quality aspects of the prey bacteria and revealed both general and prey‐specific trends in the growth responses of natural HNF communities to changing prey food quality represented by 16 distinct bacterial strains (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…) related to different temporal community dynamics of bacterivorous HNF that have been previously described (e.g., Šimek et al ; Domaizon et al ; Nolte et al ). However, the responses of the natural grazer communities to enrichment with particular prey over different plankton successional phases have rarely been demonstrated (Grujčić et al ). Additionally, comparisons of the same prey amendments in samples from the reservoir and the lake revealed significant differences in HNF growth parameters that can be related to different seasonal succession of plankton and different trophic status of the lakes (experiments III–VI, for a detailed analysis see also Grujčić et al ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations